Cell wall proteomics of crops - Komatsu, Setsuko; Yanagawa, Yuki (Frontiers in Plant Science, 2013)
Cell wall proteins play key roles in cell structure and metabolism, cell enlargement, signal transduction, responses to environmental stress, and many other physiological events. Agricultural crops are often used for investigating stress tolerance because cultivars with differing degrees of tolerance are available. Abiotic and biotic stress factors markedly influence the geographical distribution and yields of many crop species. Crop cell wall proteomics is of particular importance for improving crop productivity, particularly under unfavorable environmental conditions. To better understand the mechanisms underlying stress response in crops, cell wall proteomic analyses are being increasingly utilized. In this review, the methods of purification and purity assays of cell wall protein fractions from crops are described, and the results of protein identification using gel-based and gel-free proteomic techniques are presented. Furthermore, protein composition of the cell walls of rice, wheat, maize and soybean are compared, and the role of cell wall proteins in crops under flooding and drought stress is discussed. This review will be useful for clarifying the role of the cell wall of crops in response to environmental stresses.